PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP MINAT BELI MAKANAN TRADISIONAL DI MEY’S KITCHEN - Patrick Grady Christhoper P.; Sonata Christian (Universitas Ciputra Surabaya, 2022)
The purpose of this research is to find out the effect of product quality, price, and promotion on buying interest of traditional food at Mey's Kitchen. This research is based on pre-survey result that asks what things that can increase buying interest of Mey’s Kitchen business, so from that pre-survey is resulted three variables that can increase buying interest such as product quality, price, and promotion. As effort to collect research data, the researcher distributes 102 questionnaires to respondents who are 15 to 60 years old through online questionnaires, sampling is done by using Lemeshow theory method. The sampling technique that is used is non-probability sampling, that is, purposive sampling. The questionnaires that have been given to the respondents are stated feasible entirely and are used in this research. In t-test or partial test that is done in this research, it is found the calculation result state that the factor of product quality, that is, sig value of = 0.189, the price, that is, sig value of = 0.000, and promotion, that is sig value of = 0.000. Based on the result, it can be known that product quality does not affect significantly on traditional food buying interest of Mey's Kitchen, while price and promotion variables affect significant on buying interest. Based on the result, it can be concluded that the product quality that is available at Mey's Kitchen has been recognized for its quality and typical taste, while product price needs to be concerned from similarity side with product quality that is offered and price that must compete with similar products. For promotion, Mey's Kitchen needs to concern to the promotional content that is given and also promotional posting regularly in order to attract more buying interest of potential consumers. Keywords: buying interest, product quality, price, promotion